Evaluation of Consumers Perspective on the Consumption of Antibiotics, Antibiotic Resistance, and Recommendations to Improve the Rational use of Antibiotics: An Exploratory Qualitative Study From Post-Conflicted Region of Pakistan - Khan, Faiz Ullah; Mallhi, Tauqeer Hussain; Khan, Farman Ullah; Hayat, Khezar; Rehman, Asim.Ur; Shah, Shahid; Khan, Zakir; Khan, Yusra Habib; Ahmad, Tawseef; Gudi, Sai Krishna; Karataş, Yusuf; Fang, Yu (Frontiers in Pharmacology, 2022)
Background: Antibiotic misuse is a global challenge, and the situation is likely to deteriorate in conflict zones with insufficient health services. The misuse of antibiotics is not only associated with antimicrobial resistance but may also lead to serious consequences. This study was aimed to investigate the knowledge, attitude, and practices on antibiotic consumption, antibiotic resistance (ABR), and related suggestions among residents of conflicted zones in Pakistan. Methods: Semi-structured interviews were conducted at community pharmacies between June 2020 to January 2021. The primary findings were ascertained through thematic content analysis. Themes, sub-themes, and categories were drawn from the final analysis. Data analysis was carried out in six steps from getting to know the data to final report development. Results: A total of 20 consumers were interviewed with a mean interview duration of 25.4 minutes. The average age of participants was 35.1 years and most of them were males. The ABR was unfamiliar to the participants. Most of the participants understood the term "antibiotics" but they did not know how to use them properly. Participants were unable to distinguish between bacterial and viral illnesses. Thirteen participants believed that antibiotics have a faster effect than any other drug. Most of the participants perceived that every antibiotic could cause diarrhea, and pharmacy staff sometimes prefer another medicine like multivitamins. Consumer practices regarding antibiotic usage and ABR were found to be poor. Most participants recommended that health officials must ensure qualified staff at pharmacies with strict regulations. Five interviewees responded that a leaflet inside the medicine packing and instructions related to antibiotics in Urdu is always helpful particularly in the preparation of solutions from powder appropriately. Conclusions: This study underscored poor knowledge, attitude, and practices among residents of conflicted zones towards antibiotics and ABR. Low literacy rate, unavailability of health care facilities, absence of pharmacists at community pharmacies, and uncontrolled sales of antibiotics are some factors attributed to serious hazards, ABR, and irrational use of drugs.